New record of the genus Eudemopsis Falkovitsh (Tortricidae: Olethreutinae) from India, with description of two new species - R., Shashank P.; Naik, Santhosh (Zootaxa, 2026)
The genus Eudemopsis Falkovitsh, 1962 (Lepidoptera: Tortricidae: Olethreutinae) is recorded for the first time from India, based on the discovery of two new species, Eudemopsis hunliensis sp. nov. and Eudemopsis gobuka sp. nov. Detailed descriptions and diagnostic characters are provided, along with illustrations of adults and their genitalia. A checklist of the known species within the genus, accompanied by a taxonomic key that facilitates identification.